Easily missed pathologies of the musculoskeletal system in the emergency radiology setting - Weber, Marc-André (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2024)
The musculoskeletal region is the main area in terms of easily missed pathologies in the emergency radiology setting, because the majority of diagnoses missed in the emergency setting are fractures.A review of the literature was performed by searching the PubMed and ScienceDirect databases, using the keywords (‘missed injuries’ or ‘missed fractures’) and (‘emergency radiology’ or ‘emergency room’) and (‘musculoskeletal’ or ‘bone’ or ‘skeleton’) for the title and abstract query. The inclusion criteria were scientific papers presented in the English and German languages. Among the 347 relevant hits between 1980 and 2024 as identified by the author of this review article, there were 114 relevant articles from the years between 2018 and 2024. Based on this literature search and the author’s personal experience, this study presents useful information for reducing the number of missed pathologies in the musculoskeletal system in the emergency radiology setting.Predominant factors that make up the majority of missed fractures are ‘subtle but still visible fractures’ and ‘radiographically imperceptible fractures’. Radiologists are able to minimize the factors contributing to fractures being missed. For example, implementing a ‘four-eyes principle’, i.e., two readers read the radiographs, would help to overcome the missing of ‘subtle but still visible fractures’ and the additional use of cross-sectional imaging would help to overcome the missing of ‘radiographically imperceptible fractures’. Knowledge of what is commonly missed and evaluation of high-risk areas with utmost care also increase the diagnostic performance of radiologists.
Keywords: fractures; missed diagnoses; musculoskeletal; emergency radiology